Leaf morphology, floral biology, pollination behaviour of elite bael accessions under rainfed semi-arid conditions (Indian Journal of Arid Horticulture, 2020)
The knowledge of floral biology, pollination behaviour and reproduction biology is important for improvement and also to enhance productivity. A study was conducted on nine elite bael germplasm which were collected from Rajasthan, Uttar Pradesh and Gujarat, established through in-situ patch budding at Experimental form of CHES, Godhra. There were variability in leaf characters i.e., leaflet shape, leaf margin, leaf apex, leaf base and leaf surface among the accessions. Variation in bark colour and bark splitting pattern was also observed. Phyllotaxy in different genotypes was observed tristichous and pentastichous. Inflorescence consists of 2-31 lower buds and also single flowers. Flowers possess 4-5 petals within same accession, but 4 followed by 5 petals were found to be common in almost all studied accessions; however 3 and 6 sepals may be seen rarely in few accession. Considerable variations in size of bud, flower, petal, pedicel, stamen, filament, anther, pistil, ovary style, stigma and number of stamens/flower and pollen viability were recorded among the studied accessions. The maximum anthesis was observed between 6.31-8.30 am in all the varieties and it was continued up to 12.30 pm.
Keywords: Floral biology; leaf morphology; pollination behaviour; bael